2008
DOI: 10.4161/cc.7.13.6221
|View full text |Cite
|
Sign up to set email alerts
|

IRF6 in development and disease: A mediator of quiescence and differentiation

Abstract: Post utero development of the mammary gland is a complex developmental process characterized by states of rapid cell proliferation (branching morphogenesis) followed by functional differentiation (lactation) and the consequent apoptosis (involution) of the secretory mammary epithelial cell. This process is cyclical, such that involution returns the mammary gland to a near-virgin-like state capable of responding to morphogenic cues with each consecutive pregnancy. Importantly, many of the regulatory processes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…Recent advances (19) provide hope that direct targets of IRF6 can be identified and then assessed as potential causal genes in orofacial clefting. Since p63 and IRF6 are known to be involved in cancer (1,8,15) and in view of the present findings (9, 10), it wouldn't be surprising if the p63-IRF6 relationship were disrupted in cancer, albeit with variation inherent to neoplasia.…”
Section: Irf6 Targets P63 To Proteasomal Degradationmentioning
confidence: 84%
See 3 more Smart Citations
“…Recent advances (19) provide hope that direct targets of IRF6 can be identified and then assessed as potential causal genes in orofacial clefting. Since p63 and IRF6 are known to be involved in cancer (1,8,15) and in view of the present findings (9, 10), it wouldn't be surprising if the p63-IRF6 relationship were disrupted in cancer, albeit with variation inherent to neoplasia.…”
Section: Irf6 Targets P63 To Proteasomal Degradationmentioning
confidence: 84%
“…TGF-β signaling exerts roles in tumor suppression and metastasis, and recent findings point to a tumor suppressor function for p63, which promotes the oncogenic function of TGF-β in cancer cells when it is lost subsequent to its TGF-β-dependent sequestration by mutant p53 (15). IRF6 mRNA and protein are totally lost in metastatic breast cancer cell lines and in invasive breast ductal carcinomas (8). These observations suggest that TGF-β, p63, and IRF6 also interact in cancer.…”
Section: Abnormal Epithelial Differentiation Generates Cleft Palatementioning
confidence: 99%
See 2 more Smart Citations
“…In previous analyses, IRF6 was hypothesized to promote proliferation and development of the placenta (Fleming et al 2009). However, recent results have suggested that IRF6 functions synergistically with maspin to induce differentiation of epithelial cells by regulating exit from the cell cycle and entry into the G(0) phase of cellular quiescence (Bailey & Hendrix 2008, Biggs et al 2014.…”
Section: Discussionmentioning
confidence: 99%